Prevalence of eye disease in Brazilian patients with psoriatic arthritis (Clinics, 2012)
OBJECTIVES: The aim of this study was to report the type and frequency of ocular manifestations in Brazilian psoriatic arthritis patients. METHODS: We conducted a cross-sectional study in a Brazilian tertiary hospital. The test group included 40 patients who had psoriatic arthritis according to the Classification Criteria for Psoriatic Arthritis. A control group of 40 individuals was matched for age and gender. All of the patients underwent ophthalmic evaluation, which included best-corrected visual acuity, slit lamp and fundus examinations, and dry eye diagnostic tests (Schirmer I, tear breakup time and rose bengal). Demographic parameters were also evaluated. RESULTS: The mean age of the patients was 53.9±13.1 years; the mean disease duration was 8±10.5 years. Most of the patients were women (60%), and the majority had polyarticular disease (57.5%). Several ocular abnormalities were found, including punctate keratitis, pinguecula, blepharitis, pterygium, cataract, glaucoma, uveitis, and retinal microvascular abnormalities. There were no significant differences in the rates of these abnormalities compared with the control group, however. The Keratoconjunctivitis sicca and dry eye diagnostic tests were more often positive in the patients with psoriatic arthritis than in the control group. CONCLUSIONS: In this study, keratoconjunctivitis sicca was the most common ocular finding related to psoriatic arthritis. Therefore, we recommend early ophthalmologic evaluations for all psoriatic arthritis patients who complain of eye symptoms.